Optimizing financial performance: The interplay between financial management and accounting information systems in Yemeni SMEs - Senan, Nabil Ahmed Mareai (Asian Economic and Financial Review, 2024)
This study aims to explore the moderating effect of accounting information systems (AIS) on the relationship between financial management (FM) and its dimensions (working capital management, financial reporting, and non-current asset management) on the financial performance (FP) of small and medium enterprises in the Republic of Yemen. The study used a quantitative model approach, with data collected via a cross-sectional questionnaire to evaluate the connections within the proposed model. The data was collected from a sample of 287 individuals from SMEs according to the cluster method and analyzed with structural equation modeling (SEM) using SmartPLS software. The results revealed that financial management (non-current asset management and financial reporting) positively and significantly affects financial performance. On the contrary, there is no effect of working capital management on financial performance. More importantly, accounting information systems do not moderate the relationship between financial management and financial performance. The results of the study provide theoretical and practical implications for SME managers on how financial management dimensions and accounting information systems work together to enhance the level of financial performance in SMEs. The interaction between financial management practices and accounting information systems can empower SMEs to make more informed financial decisions. By leveraging this interaction effectively, businesses can optimize resource allocation, investment strategies, and risk management processes.